Roles of ERK signaling pathway in regulating myelination of the peripheral nervous system - Liu, Di; Zhou, Jingwei (Frontiers in Molecular Neuroscience, 2025)
Myelination of Schwann cells is a complex biological process that plays a crucial role in peripheral nervous system (PNS) development and repair. Recent studies have indicated that the extracellular signal-related kinase (ERK) signaling pathway participates in both developmental PNS myelination and remyelination. This review focuses on recent evidence identifying the roles of the ERK signaling pathway in regulating Schwann cell differentiation, myelination, and remyelination. In addition, the crosstalk between the ERK signaling pathway and other cellular signaling pathways that control Schwann cell myelination, such as c-Jun and Notch, are discussed. This review provides an overview of recent studies, revealing that dysregulated expression of the ERK signaling pathway participated in the pathogenesis of hereditary and acquired peripheral neuropathies.